PERLINDUNGAN HUKUM BAGI PENGGUNA JASA PINJAMAN ONLINE (PINJOL) - Alvina Adi Puteri; Delorens L.N Bessie; Agustin L.M Rohi Riwu (Jurnal Administrasi Terapan, 2025)
The rapid growth of online lending services in Indonesia has raised concerns regarding legal protection for consumers. This study aims to analyze the forms of legal protection available to users of online lending platforms and evaluate the effectiveness of current regulations, particularly Financial Services Authority Regulation (POJK) No. 77/POJK.01/2016 and Law No. 8 of 1999 on Consumer Protection. A qualitative descriptive approach was used in this research.The findings reveal that despite existing regulations issued by the Financial Services Authority (OJK), many illegal online lending platforms continue to operate without proper licenses. As a result, consumers remain vulnerable to fraud, excessive interest rates, and unethical debt collection practices. A significant contributing factor is the general lack of legal awareness among users.This study recommends that consumers use only registered and licensed platforms under OJK supervision. In addition, there is a need for stronger regulatory enforcement and public legal education to ensure better consumer protection and reduce harmful practices in the online lending sector.Keywords: legal protection, online lending, OJK, consumer rights